Influence of Epoxy Glue Modification on the Adhesion of CFRP Tapes to Concrete Surface - Andrzej Szewczak (MDPI AG, 2021)
Strengthening structural concrete, steel or wooden elements with reinforcement tapes is currently a popular method of extending the durability of buildings. In the glued joint Carbon Fibre Reinforced Polymer (CFRP) tape—concrete substrate, the most critical element is the adhesive layer connecting both materials. The glued joint participates in the transfer of stresses between the reinforced element and the reinforcement tape. Among the numerous analyses of this type of joint, the work resulting from the action of shear stresses (shearing) is considered most frequently, which also results from the originally developed computational models emerging with the development of research on the processes of adhesive effectiveness. The subsequent theories considered the share of other stresses, which is also related to the complex nature of the phenomenon of glue adhesion on various surfaces. Research shows the possibility of modifying the adhesion of the glue by altering its composition and the target surface of application. The study contains the results of research on the possibility of changing the adhesion of the glue to a concrete surface prepared by grinding and sandblasting. The selected epoxy resin has been modified by using the additives of microsilica and carbon nanotubes. Effective mixing of ingredients was achieved due to the use of sonication in the mixing process. Then, the adhesives prepared in this way were used to stick fragments of CFRP tape to concrete surfaces: cleaned, ground and sandblasted. A modified version of the pull-off test was used to determine the effectiveness of adhesion the CFRP tapes to concrete. The results are the final stage summarizing a series of studies including other parameters affecting the bonding efficiency and durability of adhesive bonds.